1983
DOI: 10.4319/lo.1983.28.1.0042
|View full text |Cite
|
Sign up to set email alerts
|

Production and consumption of carbon monoxide in a eutrophic lake1

Abstract: CO concentrationswere measured in the water of a eutrophic lake by a technique which allowed the detection of 30.5 nl CO* liter-l of water. In spring, when the lake was aerobic to the bottom, CO distribution was relatively homogeneous with concentrations of 40-130 nlaliter-l.In summer, CO concentrations ranged between 20 and 615 nleliter-' in the aerobic epilimnion and metalimnion, but reached values of >8,000 nl* liter-' in the anaerobic hypolimnion. CO increased during the morning and decreased during the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
3
32
2
Order By: Relevance
“…This is also in line with the presence of group 3d hydrogenases in coastal (nutrient-rich environments) and their absence in nutrient-poor open ocean regions (9). Previous studies on hydrogen concentrations in freshwater lakes found the highest concentrations near the surface that coincided with the maximum of primary production and that of the chlorophyll maximum (18,19). Daily maxima were found especially at dawn (18).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This is also in line with the presence of group 3d hydrogenases in coastal (nutrient-rich environments) and their absence in nutrient-poor open ocean regions (9). Previous studies on hydrogen concentrations in freshwater lakes found the highest concentrations near the surface that coincided with the maximum of primary production and that of the chlorophyll maximum (18,19). Daily maxima were found especially at dawn (18).…”
Section: Discussionsupporting
confidence: 62%
“…Both could enable the respective bacteria to participate in hydrogen oxidation and could open access to an additional energy source. Therefore, hydrogen consumption in surface waters as measured in a number of studies of freshwater lakes (18,19) probably originates from these two groups of [NiFe]-hydrogenases expressed in Burkholderiales, acidobacteria, and actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of intra-and interspecies hydrogen cycling, most microbial H 2 -oxidizing and H 2 -producing processes are balanced and hence make minor or null net contributions to the global hydrogen budget (5). It has nevertheless been known for several decades that soil ecosystems can oxidize tropospheric H 2 in an apparent enzymatic process (6)(7)(8). This ecologically essential process is estimated to be accountable for 80% of the net loss of tropospheric H 2 (3).…”
mentioning
confidence: 99%